Regulation of the Central Carbon Metabolism in Apple Fruit Exposed to Postharvest Low-Oxygen Stress - Boeckx, Jelena; Pols, Suzane; Hertog, Maarten L. A. T. M.; Nicolaï, Bart M. (Frontiers in Plant Science, 2019)
After harvest, fruit remain metabolically active and continue to ripen. The main goal of postharvest storage is to slow down the metabolic activity. In many cases, this is accomplished by storing fruit at low temperature in combination with low oxygen (O2) and high carbon dioxide (CO2) partial pressures. However, altering the normal atmospheric conditions is not without any risk and can induce low-oxygen stress. This review, therefore, focusses on the central carbon metabolism of fruit, both under normal oxygen conditions and under low-oxygen stress conditions. First, the general context of postharvest fruit storage will be introduced. After reviewing the central carbon metabolism and the impact of low-oxygen stress on it, recent literature on oxygen sensing will be discussed. While many of the elements presented will be applicable to other fruit as well, the current review is focused on apple fruit.